Electrochemical Sample Matrix Elimination for Trace-Level Potentiometric Detection with Polymeric Membrane Ion-Selective Electrodes - Chumbimuni-Torres, K.; Calvo-Marzal, P.; Wang, J.; Bakker, Eric (American Chemical Society, 2008)
Potentiometric sensors are today sufficiently well understood and optimized to reach ultratrace level (subnanomolar) detection limits for numerous ions. In many cases of practical relevance, however, a high electrolyte background hampers the attainable detection limits. A particularly difficult sample matrix for potentiometric detection is seawater, where the high saline concentration forms a major interfering background and reduces the activity of most trace metals by complexation. This paper describes for the first time a hyphenated system for the online electrochemically modulated preconcentration and matrix elimination of trace metals, combined with a downstream potentiometric detection with solid contact polymeric membrane ion-selective microelectrodes. Following the preconcentration at the bismuth-coated electrode, the deposited metals are oxidized and released to a medium favorable to potentiometric detection, in this case calcium nitrate. Matrix interferences arising from the saline sample medium are thus circumvented. This concept is successfully evaluated with cadmium as a model trace element and offers potentiometric detection down to low parts per billion levels in samples containing 0.5 M NaCl background electrolyte.